2021
DOI: 10.9744/jmk.23.1.18-26
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Influencer, Brand Awareness, and Purchase Decision Among Generation Z in Surabaya

Abstract: Many restaurants and cafes use Social Media Influencer (SMI) services to promote their products/ services. The three dimensions of SMI include reach, relevance, and resonance; and these can influence brand awareness and purchase decision of generation Z consumers. This study involved 108 respondents and used SPSS and Partial Least Square (PLS) as data analysis techniques. The results of this study indicate that reach, relevance and resonance of SMI have positive and significant influences on brand awareness. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
0
19
0
3
Order By: Relevance
“…Due to this, increasing numbers of Muslims have turned toward dedicated halal influencers on social media for help in navigating the increasingly complex rules and processes surrounding contemporary halal practices (Rahim et al, 2021; Rohman & Ulinnuha, 2022). Previous studies have found that these social media influencers shape the choice of halal products by Muslims (Fitriyani, 2021; Gunawan et al, 2021) and that they play an important role in educating the public on halal issues (Rohman & Ulinnuha, 2022). Therefore, considering the substantial influence of family members, friends, and halal influencers in shaping Muslims’ decisions regarding food choices, we propose the following hypothesis:…”
Section: The Influence Of Presumed Media Influence Modelmentioning
confidence: 99%
“…Due to this, increasing numbers of Muslims have turned toward dedicated halal influencers on social media for help in navigating the increasingly complex rules and processes surrounding contemporary halal practices (Rahim et al, 2021; Rohman & Ulinnuha, 2022). Previous studies have found that these social media influencers shape the choice of halal products by Muslims (Fitriyani, 2021; Gunawan et al, 2021) and that they play an important role in educating the public on halal issues (Rohman & Ulinnuha, 2022). Therefore, considering the substantial influence of family members, friends, and halal influencers in shaping Muslims’ decisions regarding food choices, we propose the following hypothesis:…”
Section: The Influence Of Presumed Media Influence Modelmentioning
confidence: 99%
“…The inclination to purchase goods or services is likely to be higher when the customers find that the revenue is significantly higher than their sacrifice (Hasena & Sakapurnama, 2021). Furthermore, customers' choice of numerous alternatives to meet their needs can be categorized as purchasing decisions (Andreani et al, 2021). Also, when consumers decide to buy goods, then they will look for the details needed based on their experiences and the external surroundings (Choedon & Lee, 2020).…”
Section: Purchase Intentionmentioning
confidence: 99%
“…Influencers are social media users who have many followers and can influence many people. Influencers open up opportunities to work with companies in promoting marketed product/service brands (Andreani, Gunawan, & Haryono, 2021). Hotel A uses influencers as a promotional medium for the company to maintain brand awareness and increase sales.…”
Section: Crisis Management Strategymentioning
confidence: 99%